2018
DOI: 10.1080/02678292.2018.1524523
|View full text |Cite
|
Sign up to set email alerts
|

The induction of the Ntbphase in mixtures

Abstract: The induction of the Ntb phase in mixturesWe report the induction of the Ntb phase over a wide temperature and concentration range in a binary system. This was achieved by addition of a flexible dopant without LC properties to a flexible dimer exhibiting only a nematic LC phase. The Ntb phase was identified by POM, DSC and XRD techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 52 publications
(55 reference statements)
0
13
1
Order By: Relevance
“…Finally, it should be noted that breaking one (or more) of the symmetries of the N phase (nonchirality, uniaxiality, a‐polarity) can lead to a variety of more highly ordered nematic phases. such as i) the chiral nematic phase (discussed below), ii) biaxial nematic phases, [ 65,66 ] which are defined by two directors perpendicular to each other and have been identified experimentally in colloidal board‐like systems, [ 67,68 ] a ternary lyotropic system that formed board‐like micelles [ 69 ] and in thermotropic banana‐shaped systems, [ 70 ] iii) the nematic twist‐bend [ 61,71–76 ] a chiral phase formed by achiral mesogens, characterized by a helical modulation of the orientational order with a pitch of the order of 10 nm.…”
Section: The Liquid Crystalline Statementioning
confidence: 99%
“…Finally, it should be noted that breaking one (or more) of the symmetries of the N phase (nonchirality, uniaxiality, a‐polarity) can lead to a variety of more highly ordered nematic phases. such as i) the chiral nematic phase (discussed below), ii) biaxial nematic phases, [ 65,66 ] which are defined by two directors perpendicular to each other and have been identified experimentally in colloidal board‐like systems, [ 67,68 ] a ternary lyotropic system that formed board‐like micelles [ 69 ] and in thermotropic banana‐shaped systems, [ 70 ] iii) the nematic twist‐bend [ 61,71–76 ] a chiral phase formed by achiral mesogens, characterized by a helical modulation of the orientational order with a pitch of the order of 10 nm.…”
Section: The Liquid Crystalline Statementioning
confidence: 99%
“…Ramou et al. reported that the N TB phase can be induced in mixtures of conventional nematic and nonmesogenic dimers . Besides liquid‐crystal dimers, the N TB phase has also been observed in bent‐core molecules, oligomers, and polymers .…”
Section: Introductionmentioning
confidence: 99%
“…[16] Ramou et al reported that the N TB phase can be induced in mixtures of conventionaln ematic and nonmesogenic dimers. [17] Besides liquid-crystal dimers, the N TB phase has also been observedi nb ent-core molecules, [5,[18][19][20] oligomers, [21][22][23][24][25] and polymers. [3,4,26] Although the majority of twist-bend nematogens developeds of ar are achiral,t here have been af ew reports on formation of the N TB phase based on chiral bentshaped molecules,i nw hicht he chirality is located in the mesogenic-arm core, [27,28] terminal chain, [29] or spacer.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore sought a new method to obtain splay nematic materials; induction of the NS phase in mixtures of two materials that do not exhibit this phase, in a similar vein to the induction of the twist-bend nematic phase in binary mixtures. [19][20][21]…”
Section: Introductionmentioning
confidence: 99%